Identifying Plasmodium falciparum merozoite surface antigen 3 (MSP3) protein peptides that bind specifically to erythrocytes and inhibit merozoite invasion (2005)
Receptor–ligand interactions between synthetic peptides and normal human erythrocytes were studied to determine Plasmodium falciparum merozoite surface protein?3 (MSP?3) FC27 strain regions that specifically bind to membrane surface receptors on human erythrocytes. Three MSP?3 protein high activity binding peptides (HABPs) were identified; their binding to erythrocytes became saturable, had nanomolar affinity constants, and became sensitive on being treated with neuraminidase and trypsin but were resistant to chymotrypsin treatment. All of them specifically recognized 45?, 55?, and 72?kDa erythrocyte membrane proteins. They all presented ??helix structural elements. All HABPs inhibited in vitro P. falciparum merozoite invasion of erythrocytes by ?55%–85%, suggesting that MSP?3 protein's role in the invasion process probably functions by using mechanisms similar to those described for other MSP family antigens.